2019
DOI: 10.1104/pp.19.00688
|View full text |Cite
|
Sign up to set email alerts
|

PERSISTENT TAPETAL CELL2 Is Required for Normal Tapetal Programmed Cell Death and Pollen Wall Patterning

Abstract: The timely programmed cell death (PCD) of the tapetum, the innermost somatic anther cell layer in flowering plants, is critical for pollen development, including the deposition and patterning of the pollen wall. Although several genes involved in tapetal PCD and pollen wall development have been characterized, the underlying regulatory mechanism remains elusive. Here we report that PERSISTENT TAPETAL CELL2 (PTC2), which encodes an AT-hook nuclear localized protein in rice (Oryza sativa), is required for normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 52 publications
1
50
0
1
Order By: Relevance
“…3V). Similarly, Uzair et al [34] found marginal differences in the patterning of nano-ridges on the outer surface, as well as in the distribution of Ubisch bodies, on the inner surface of anthers in rice ptc2 mutants, which resulted in decreased pollen viability in comparison with that of wild-type plants. However, in SY63 plants, HT had no substantial effect on Ubisch bodies or anther cuticles (Fig.…”
Section: The Relationship Of Pollen Viability With Anther Characterismentioning
confidence: 85%
See 2 more Smart Citations
“…3V). Similarly, Uzair et al [34] found marginal differences in the patterning of nano-ridges on the outer surface, as well as in the distribution of Ubisch bodies, on the inner surface of anthers in rice ptc2 mutants, which resulted in decreased pollen viability in comparison with that of wild-type plants. However, in SY63 plants, HT had no substantial effect on Ubisch bodies or anther cuticles (Fig.…”
Section: The Relationship Of Pollen Viability With Anther Characterismentioning
confidence: 85%
“…The tapetum, the innermost layer in the anther wall, serves as an active nutrient source for neighboring microspores [34,39], and abnormal tapetum degeneration results in pollen sterility in photoperiod and thermosensitive genic male-sterile rice [40,41] and rice mutants [34]. These previous reports indicate that termination of secretory-type tapetum development and disruption of tapetal functions is partly responsible for pollen viability.…”
Section: The Relationship Of Pollen Viability With Anther Characterismentioning
confidence: 86%
See 1 more Smart Citation
“…We speculate that TDR regulates pollen wall formation by activating the expression of OsMS188 during anther development. Additionally, GAMYB and PTC2 have also been reported to regulate exine formation and PCD of tapetal cells in rice anther development (Aya et al 2009;Uzair et al 2020). PTC2 is the homologue of TEK, an AT-hook motif nuclear-localized protein essential for nexine formation in Arabidopsis.…”
Section: The Transcriptional Regulatory Pathway Of Rice Tapetum Develmentioning
confidence: 99%
“…Key players and developmental programs for early anther development have been extensively studied and described (reviewed in : Timofejeva et al 2013;Kelliher et al 2014;Walbot and Egger 2016; van der Linde and Walbot 2019) (Table 1). Other studies gave insight into late anther and pollen development (for example, see: Dickinson and Bell 1976;Schreiber et al 2004), and by now also provide a sound understanding about involved transcription factors and components for the tapetal cell death and pollen wall formation (for example, Huo et al 2020;Xiong et al 2020;Uzair et al 2020;Lu et al 2020). A recurring Communicated by Dolf Weijers.…”
Section: Introductionmentioning
confidence: 99%